Acupuncture Combined with Traditional Chinese Medicine and Drug Therapy for the Treatment of Cerebral Infarction (Phlegm-Blood Stasis Syndrome) and Carotid Atherosclerotic Plaque: A Preliminary Randomized Controlled Study - Wentong Wang; Zhuli Liu; Yongxiong Wu (Applied Bionics and Biomechanics)
Carotid atherosclerotic plaque (CAP) is one of the leading causes of cerebral infarction. Western medicine usually uses lipid-lowering drugs to stabilize plaques. Currently, studies reporting on drugs that can reduce plaques are lacking. Here, we performed a randomized controlled study to investigate the effectiveness of acupuncture combined with drug therapy (TCM and Western) to treat cerebral infarction (phlegm-blood stasis syndrome) and CAP. The control group was treated with atorvastatin calcium tablets (20 mg/d, po for 15 days). The treatment group received atorvastatin calcium tablets 20 mg, traditional Chinese medicine (TCM) decoctions (two matured substance decoction plus peach kernel and Carthamus four substance decoction plus Chinese hawthorn fruit 20 g, gold theragran 20 g, and red yeast rice 3 g), and acupuncture therapy, once daily for 15 days as one treatment course. The patients’ neurological deficit score, ultrasonic testing of the carotid artery, and lipoprotein-associated phospholipase A2 (Lp-PLA2) were evaluated. Our findings showed no significant difference in the evaluated indices between the two groups before treatment (P>0.05). However, compared with the control group after 15 days of treatment and within each group before and after treatment, the differences were significant (P<0.05). In conclusion, acupuncture combined with drug therapy demonstrated promising effectiveness in treating cerebral infarction (phlegm-blood stasis syndrome) and CAP.